Utilization of wind energy for irrigation in India (MAUSAM, 1982)
The energy potential available from windmills in different States based on long term India Met. Dep. wind data has been estimated and presented in this paper, The water requirements for crops grown in the different States and the energy needed to meet these demands are calculated. It is shown that wind energy generated will meet the irrigation needs of crops grown in the different States, quite adequately. Suitable escarpments to increase wind speeds which in turn increase power is discussed. Large scale manufacture of low-cost high efficiency windmills which are capable of operating even in low wind speeds is also suggested in the paper.